Several Functions of Rhizopus sp on Increasing Nutritional Value of Feed Ingredient - Dwi Endrawati; Eni Kusumaningtyas (WARTAZOA, Indonesian Bulletin of Animal and Veterinary Sciences, 2017)
Rhizopus sp is a type of fungi which easily grow in the soil, fruit, vegetables and fermented food. This paper describes some functions of Rhizopus sp on increasing nutritional value of feed ingredient and possibility of its application in Indonesia. Rhizopus mold has been known in Indonesia especially for tempe production for food. Research about Rhizopus sp gives knowledge for utilizing Rhizopus sp for other functions. Rhizopus sp is able to inhibit the growth of toxigenic fungus, Aspergillus flavus and to degrade aflatoxin. Rhizopus sp also produces compounds which are able to inhibit pathogenic bacteria and acts as antioxidant. Rhizopus sp absorbs some minerals and changes them to become organic minerals hence it increases mineral absorption by the body. Utilization of feed fermented by Rhizopus sp in livestock showed better result compared to non fermented feed. Rhizopus sp is also very potential to be applied as feed additive for livestock.